Precedent Phenomena: Transformation Processes - T. I. Svistun; I. L. Ilyicheva (Дискурс)
Introduction. The precedent phenomenon in the title of a journalistic article is one of the characteristic features of the modern Belarusian mass media discourse. The article examines the pecularities of transformation processes of precedent phenomena in republican and regional newspapers.Methodology and sources. The theoretical basis of this research was formed by the works in the field of discourse theory (T. van Dijk, T. G. Dobrosklonskaya, V. E. Chernyavskaya), as well as the theory of intertextuality and precedence (M. M. Bakhtin, Y. Kristeva, R. Bart, I. V. Arnold, D. B. Gudkov). In the course of the study, a structural and semantic analysis of the headings and a content analysis of the articles of Belarusian newspapers were carried with the focus on difference between center and periphery. The research material was the republican and regional newspapers of Belarus in the period from 2017 to 2020 years (a total of 400 articles with heading complexes).Results and discussion. The activity of precedent information in the Belarusian journalism of the period under review is evidenced by numerous references, allusions, intertextual inclusions recorded in various republican and regional media, both unchanged and transformed. In the case of transformation, the elements of the original text, name, statement, situation can be shortened, replaced or addition may take place. In some cases, to draw attention to the media text, the author uses transformations not only at the lexical, but also at the phonetic, morphemic, syntactic levels. In general, transformed precedent phenomena prevail in Belarusian publications (about 75 %). The most subject to transformation are precedent statements and texts, and the least – situations. These tendencies are typical for both republican and regional publications.Conclusion. The application of the precedent phenomenon actualizes the background knowledge of the reader, referring to the phenomena that have already received a certain interpretation and assessment. The transformation of the precedent phenomenon allows you to link information about the event or the fact described by the author with the information already available in the linguo-cognitive base, updating and multiplying it, expanding and enriching the communicative space.